Examining systematic risk on Malaysian firms: panel data evidence - Ibrahim, Khairunisah; Haron, Razali (Global Business and Social Entrepreneurship (GBSE), 2016)
This study is motivated by the issue of inconclusiveness in the literature pertaining to the impact of firm specific variables towards the systematic risk, with a specific focus given on the financial leverage and firms’ financing policies. By employing panel data and Fixed Effect Model (FEM), this study examines comprehensively the determinants of systematic risk of 824 non-financial listed firms in Malaysia, for the period of fourteen years, from 2000 until 2013. To gain an inclusive understanding on the systematic risk, inter-industry variations is also investigated using the FEM. Overall findings reveal that financial leverage is the most significant variable influencing the systematic risk of Malaysian firms. Other controlling variables are not found to be significant. However, interestingly, results from the inter-industry analysis shows different views with some significant impact from other firm specific controlling variables for certain industries. Findings from this study add to the literature on systematic risk, especially on the inter-industry differences in relation to the factors influencing the firms’ exposures to the systematic risk.